2015
DOI: 10.4238/2015.december.14.4
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased miR-134 expression and its tumor-suppressive function in human osteosarcoma

Abstract: ABSTRACT. Dysregulation of microRNA (miR) is often associated with cancer development and progression. Aberrant expression of miR-134 has been found in some types of cancer. However, its expression and function in osteosarcoma remain unclear. The aim of this study was to explore the effects of miR-134 in osteosarcoma tumorigenesis and development. The expression level of miR-134 was quantified by real-time reverse transcription-polymerase chain reaction in human osteosarcoma cell lines and tissues. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Previous research has identified consistently decreased miR-134 expression in many types of cancers (11)(12)(13). To investigate miR-134 expression in GC, we collected 26 human GC specimens and pair-matched gastric adjacent non-neoplastic mucosa.…”
Section: Mir-134 Is Downregulated In Gcmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous research has identified consistently decreased miR-134 expression in many types of cancers (11)(12)(13). To investigate miR-134 expression in GC, we collected 26 human GC specimens and pair-matched gastric adjacent non-neoplastic mucosa.…”
Section: Mir-134 Is Downregulated In Gcmentioning
confidence: 89%
“…Previous studies identified a close relationship between miR-134 and the progression of various types of cancers. In patients with colorectal cancer, osteosarcoma and breast cancer, miR-134 was found to be decreased and to act as a tumor-suppressor (11)(12)(13). In the present study, we provide evidence that miR-134 is downregulated in GC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of miR-134 presented bulky carcinoma size and terminal clinicopathological period, while the lower was inverse. Moreover, decreased miR-134 expression contributed to lower total survival, which uncovered it might be a promising biomarker and approach in osteosarcoma therapy and prognosis 92 . Gunawan and colleagues 93 found that deletions of chromosomal regions 14q were apt to happen in gastric carcinoma and that they were tightly related to cytogenetical evolution, while they did not apparently correlate with lesser disease-free survival.…”
Section: Main Textmentioning
confidence: 99%
“…It exhibits oncogenic activity in head and neck carcinoma and lung adenocarcinoma 9 , 10 , 11 as well as tumor suppressive activity in breast cancer, glioma, hepatocellular carcinoma, osteosarcoma and renal cell carcinoma. 8 , 12 , 13 , 14 , 15 …”
mentioning
confidence: 99%